Measurement of pharyngeal segments in obstructive sleep apnea - Rodrigues, Marcos Marques; Moura, Lucas Borin [UNESP]; Oliveira, Ariane De Souza [UNESP]; Gabrielli, Marisa Aparecida Cabrini [UNESP]; Pereira Filho, Valfrido Antonio [UNESP]; Passeri, Luis Augusto (Editora Cubo, 2018)
Objective: Obstructive Sleep Apnea (OSA) occurs by recurrent collapse of the upper airway during sleep. It results in complete (apnea) or partial (hypopnea) reduction of airflow and has intimate relation with the upper airway anatomy. Cephalometric analysis has been used to quantify airway dimensions. The aim of this study is evaluate the correlation between the anteroposterior dimension of the upper airway and the severity of obstructive sleep apnea. Material and Methods: A retrospective analysis was performed reviewing polysomnographic data (AHI) and anteroposterior cephalometric measurementsof pharynx subregions: nasopharynx, oropharynx, hypopharynx. Results: The sample consisted of 30 patients. The mean body mass index was 29.60 kg/m2 and the average age was 46.8 years. Nine patients presented severe OSA, seven had moderate OSA, seven had mild OSA, and seven were healthy. The Pearson’s correlation index between the anteroposterior dimension of the nasopharynx, oropharynx and hypopharynx and AHI was respectively -0.128 (p=0.517), -0.272 (p=0.162) and -0.129 (p=0.513). Conclusion: The correlation between anteroposterior linear dimension of the airway and OSA severity, assessed by AHI, was not positive. As an isolated parameter it did not correlate to the severity of the obstrucive sleep apnea syndrome and should be evaluated in conjunction with other factors.
Mensuração dos segmentos faríngeos na Apneia Obstrutiva do Sono
Keywords: Cone beam CT; Obstructive sleep apnea; Upper airway